2015
DOI: 10.1089/ars.2015.6375
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein K and Protein Palmitoylation

Abstract: Significance: Selenoprotein K (SelK) is an endoplasmic reticulum (ER) membrane protein, and its expression is sensitive to dietary selenium levels. A recently described role for SelK as a cofactor in catalyzing protein palmitoylation reactions provides an important link between low dietary selenium intake and suboptimal cellular functions that depend on this selenoprotein for palmitoylation. Recent Advances: A recent breakthrough provided insight into the contribution of SelK to calcium (Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 44 publications
(65 reference statements)
0
40
0
Order By: Relevance
“…There are a few DHHC proteins whose PAT activity has been reported to require a cofactor [42,85,86] although the majority of DHHC proteins appear to have a catalytic activity independently without other protein cofactors [87]. Yeast Ras is palmitoylated by a PAT Erf2 in a form of complex with Erf4 as a cofactor [56].…”
Section: Dhhc Patsubstrate Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few DHHC proteins whose PAT activity has been reported to require a cofactor [42,85,86] although the majority of DHHC proteins appear to have a catalytic activity independently without other protein cofactors [87]. Yeast Ras is palmitoylated by a PAT Erf2 in a form of complex with Erf4 as a cofactor [56].…”
Section: Dhhc Patsubstrate Pairsmentioning
confidence: 99%
“…GCP16 as a cofactor is required for DHHC9 autopalmitoylation and Ras palmitoylation [85]. Recently, another PAT DHHC6 has been shown to palmitoylate the Ca 2+ channel protein, inositol-1,4,5-triphosphate receptor (IP3R) in the ER membrane, and the selenoprotein K (Selk) whose expression is sensitive to dietary selenium levels functions as a cofactor in the DHHC6-mediated IP3R palmitoylation as revealed by that Selk deficiency decreased palmitoylation and stability of the IP3R [42,86]. Interestingly, Selk contains an SH3 domain while DHHC6 is also predicted to contain an SH3 domain.…”
Section: Dhhc Patsubstrate Pairsmentioning
confidence: 99%
“…Selenium is an essential micronutrient that exists in the form of diverse metabolites and selenoproteins within the body (5)(6)(7)(8). Selenoproteins exhibit disulfide oxidoreductase, peroxidase, and deiododinase activities in addition to other functions such as regulation of intracellular calcium flux and protein palmitoylation (9). Previous studies have shown that selenium exerts an anti-inflammatory effect by down-regulating the expression of pro-inflammatory mediators (10).…”
mentioning
confidence: 99%
“…Later, it became clear that even a peroxidase, namely GPx4, does not always act as a peroxidase but also moonlights during sperm development to a nonenzymatic structural protein in the midpiece of mature spermatozoa. More examples of nonantioxidant roles of selenoproteins rise on the horizon and are compiled here: (i) the functional switch of TrxR1 after modification of the Sec (3); (ii) the coordinated action of MsrB1 and Micals in the regulation of the function of actin (6); (iii) the interaction of selenoproteins with proteins in membranes (7); and (iv) the role of SelK in the palmitoylation of proteins in the endoplasmic reticulum (ER) membrane (5).…”
Section: Selenoprotein Biosynthesis and Related Topicsmentioning
confidence: 99%
“…In this Forum, therefore, most striking novelties on selenoprotein biosynthesis, including the possible role of selenocysteine-b-lyase (Scly) not only in the biosynthesis of selenoproteins but also in linking selenoproteins to energy metabolism, are summarized. Regarding novel functions, the Forum particularly focuses on thioredoxin reductase 1 (TrxR1) (3), methionine sulfoxide reductase B1 (MsrB1) (6), selenoprotein K (SelK) (5), and other membrane-associated selenoproteins (SelS, SelI, SelN, and SelT) (7).…”
mentioning
confidence: 99%